A comparison of Plasmodium falciparum circumsporozoite protein-based slot blot and ELISA immuno-assays for oocyst detection in mosquito homogenates. (December 2015) - Stone, Will; Grabias, Bryan; Lanke, Kjerstin; Zheng, Hong; Locke, Emily; Diallo, Diadier; Birkett, Ashley; Morin, Merribeth; Bousema, Teun; Kumar, Sanjai
Abstract Background The infectivity ofPlasmodium gametocytes is typically determined by microscopically examining the midguts of mosquitoes that have taken a blood meal containing potentially infectious parasites. Such assessments are required for the development and evaluation of transmission-reducing interventions (TRI), but are limited by subjectivity, technical complexity and throughput. The detection of circumsporozoite protein (CSP) by enzyme-linked immunosorbent assay (ELISA) and enhanced chemiluminescent slot-blot (ECL-SB) may be used as objective, scalable alternatives to microscopy for the determination of infection prevalence. Methods To compare the performance of the CSP ELISA and ECL-SB for the detection of mosquito infection, four groups ofAnopheles stephensi mosquitoes were infected with culturedPlasmodium falciparum gametocytes. At day-8 post-infection (PI), parasite status was determined by microscopy for a sample of mosquitoes from each group. At days 8 and 10 PI, the parasite status of separate mosquito samples was analysed by both CSP ELISA and ECL-SB. Results When mosquito samples were analysed 8 days PI, the ECL-SB determined similar infection prevalence to microscopy; CSP ELISA lacked the sensitivity to detect CSP in all infected mosquitoes at this early time point. When mosquitoes were analysed 48 h later (10 days PI) both assays performed as well as microscopy for infection detection. Conclusions Whilst microscopical examination of mosquito guts is of great value when quantification of parasite burden is required, ECL-SB and CSP ELISA are suitable alternatives at day 10 PI when infection prevalence is the desired endpoint, although CSP ELISA is not suitable at day 8 PI. These results are important to groups considering large-scale implementation of TRI.